Normal, high and ultra-high modulus carbon fiber-reinforced polymer laminates for bonded and un-bonded strengthening of steel beams - Ghafoori, Elyas; Motavalli, Masoud (Materials in engineering, 2015)
•Normal, high and ultra-high modulus CFRP laminates for strengthening of steel beams.•Bonded and un-bonded reinforcement systems for steel beams.•Comparisons between the static behavior of the bonded and un-bonded systems. This paper studies the elastic behavior of steel beams strengthened with normal, high and ultra-high modulus CFRP laminates using bonded and un-bonded systems. The elastic behavior of retrofitted beams provides useful information for design of fatigue strengthening systems. A total of seven steel beams including one control unstrengthened beam and six strengthened beams were tested statically until failure in a simply supported four-point bending set-up. The steel beams were retrofitted by normal modulus (NM), high modulus (HM) and ultra-high modulus (UHM) carbon fiber-reinforced polymer (CFRP) laminates with nominal Young’s moduli, ranging from 165 to 440GPa. Each type of laminate was attached to the steel beams using bonded reinforcement (BR) and un-bonded reinforcement (UR) systems. There is no direct comparison between the BR and the UR systems in the literature. The main goal of the paper is to provide a better understating about the stress distribution along the beam bottom flange when the BR and the UR systems are used for strengthening. All specimens failed due to lateral-torsional buckling (LTB). The effect of different strengthening methods on buckling capacity of the retrofitted specimens was also studied. Experimental results have shown that strengthening using bonded UHM laminates could increase the stiffness of the composite section so that the steel profile has yielded prior to buckling and a larger reinforcement efficacy was then achieved.